2001
DOI: 10.1038/modpathol.3880330
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Expression of MDM2 in Prostate Carcinoma

Abstract: Mutation of p53 is rare in localized prostate carcinoma. The oncoprotein MDM2, whose gene has a response element for p53, promotes the degradation of p53 protein and inhibits its transcriptional activation of genes related to cell cycle arrest and apoptosis, constituting a negative feedback control. We studied p53 and MDM2 expression by immunohistochemistry and looked for mutations in p53 exons 5 to 8 by polymerase chain reaction-single strand conformational polymorphism in 118 patients submitted to radical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 38 publications
1
76
0
2
Order By: Relevance
“…Deletion or hypermethylation also represents a potential mechanism of removal of the p14ARF protein in a small proportion (16%) of prostate cancers (Konishi et al, 2002). Mutation and altered expression of other upstream regulators of pRB such as p53, p21 and MDM2 (Gao et al, 1995;Osman et al, 1999;Leite et al, 2001) have also been observed in prostate cancer, although mutations in the p53 gene are most frequently associated with metastatic and hormone-refractory disease (Heidenberg et al, 1995). It is particularly significant that prostate cancer exhibits both downregulation of pRB (Brooks et al, 1995;Theodorescu et al, 1997) and overexpression of E2F3.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion or hypermethylation also represents a potential mechanism of removal of the p14ARF protein in a small proportion (16%) of prostate cancers (Konishi et al, 2002). Mutation and altered expression of other upstream regulators of pRB such as p53, p21 and MDM2 (Gao et al, 1995;Osman et al, 1999;Leite et al, 2001) have also been observed in prostate cancer, although mutations in the p53 gene are most frequently associated with metastatic and hormone-refractory disease (Heidenberg et al, 1995). It is particularly significant that prostate cancer exhibits both downregulation of pRB (Brooks et al, 1995;Theodorescu et al, 1997) and overexpression of E2F3.…”
Section: Discussionmentioning
confidence: 99%
“…Many E3 ubiquitin ligases in the UPP have been implicated in cell cycle control and uncontrolled cell proliferation. Some E3 ligases such as MDM2 and SKP2, which target p53 and CDKN1A/CDKN1B, are considered oncoproteins (Leite et al, 2001;Lu et al, 2002;Drobnjak et al, 2003), while some other E3 ligases are considered tumor suppressors. WWP1 is an E3 ubiquitin ligase that contains four tandem WW domains and a HECT domain.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, p21 was detected in the control cells, suggesting that there are p53-independent mechanisms involved in the regulation of p21 expression as has been suggested elsewhere. 19 Furthermore, our data indicate that foreskin fibroblasts respond to irradiation in an expected fashion, indicating normal function of the p53 pathway. 20 In these cells, levels of p53 increased dramatically following 5 Gy irradiation from an undetectable level at baseline (Figure 4).…”
Section: Discussionmentioning
confidence: 83%
“…14 -16 In the normal state, the detection of the p53 protein is difficult due to its very short half-life. 13 Furthermore, p53 does not act in isolation but is under negative feedback control through the action of a variety of downstream elements, two of which are mdm-2 and p21 19 (Figure 1). One of the classic techniques to determine the functional status of the p53 protein is to expose the cells to sub-lethal DNA damage, as occurs with radiation, and to then assess p53 levels.…”
Section: Introductionmentioning
confidence: 99%